Mechatronic Design of a Mobile Platform for Assisted Labors in Coffee Crops - Rueda Sánchez, Oscar Eduardo; Ruíz Romero, Brajan Nicolás; Roa Prada, Sebastian; Hernández Barbosa, Jeyson (Revista Mutis, 2023)
Harvesting tasks in coffee crops in Colombia are conducted manually. Unfortunately, at the moment there is a low supply of labor to carry out these tasks. That is why this article describes the process of designing a mobile platform to help mitigate the aforementioned problem. There are many ways to design the platform, therefore, choosing the most suitable morphology is of vital importance. For this, the design team used the APTE methodology to select, without bias, the morphology that best met the design criteria and the parameters found when analyzing the user’s needs and the particular operating conditions of the platform. Similarly, the topology and physical layout of the mobile platform components were selected based on structural design and analysis criteria obtained from a CAD model. The results of the applied methods served as the basis for building the prototype of the mobile platform that aims to solve the problem.